Presence of Phylloquinone in the Intraerythrocytic Stages of Plasmodium falciparum - Sussmann, Rodrigo A. C.; Gabriel, Heloisa B.; Ríos, Alejandro García; Menchaca Vega, Danielle S.; Yamaguchi, Lydia F.; Doménech-Carbó, Antonio; Cebrián-Torrejón, Gerardo; Kimura, Emilia A.; Kato, Massuo J.; Bofill Verdaguer, Ignasi; Crispim, Marcell; Katzin, Alejandro M. (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria is one of the most widespread parasitic diseases, especially in Africa, Southeast Asia and South America. One of the greatest problems for control of the disease is the emergence of drug resistance, which leads to a need for the development of new antimalarial compounds. The biosynthesis of isoprenoids has been investigated as part of a strategy to identify new targets to obtain new antimalarial drugs. Several isoprenoid quinones, including menaquinone-4 (MK-4/vitamin K2), α- and γ-tocopherol and ubiquinone (UQ) homologs UQ-8 and UQ-9, were previously detected in in vitro cultures of Plasmodium falciparum in asexual stages. Herein, we described for the first time the presence of phylloquinone (PK/vitamin K1) in P. falciparum and discuss the possible origins of this prenylquinone. While our results in metabolic labeling experiments suggest a biosynthesis of PK prenylation via phytyl pyrophosphate (phytyl-PP) with phytol being phosphorylated, on the other hand, exogenous PK attenuated atovaquone effects on parasitic growth and respiration, showing that this metabolite can be transported from extracellular environment and that the mitochondrial electron transport system (ETS) of P. falciparum is capable to interact with PK. Although the natural role and origin of PK remains elusive, this work highlights the PK importance in plasmodial metabolism and future studies will be important to elucidate in seeking new targets for antimalarial drugs.